Preparedness And Resilience In Seasonal Viral Outbreaks: A Multidisciplinary Review Of Healthcare Departments As Frontline Defenders (The Review of Diabetic Studies, 2025)
Seasonal viral outbreaks, including influenza, RSV, and emerging respiratory viruses, pose recurrent challenges to healthcare systems worldwide. Effective preparedness and resilience require coordinated action across all healthcare departments rather than isolated clinical responses. This multidisciplinary review synthesizes current evidence on healthcare system readiness for seasonal viral threats, focusing on clinical preparedness, organizational coordination, workforce capacity, and digital enablement. Using a structured review methodology, the study examines how hospitals and healthcare networks mobilize frontline departments to prevent transmission, maintain service continuity, and protect patient and staff safety during seasonal viral surges. Findings highlight that preparedness is a system-level capability shaped by infection control practices, interdepartmental collaboration, surge capacity planning, staff training, supply chain robustness, and real-time surveillance technologies. The review proposes an integrated preparedness and resilience framework positioning healthcare departments as frontline defenders operating within a coordinated governance and response architecture. By synthesizing multidisciplinary evidence, this article contributes to the growing literature on health system resilience and offers actionable insights for policymakers, hospital leaders, and healthcare administrators seeking to strengthen preparedness for recurring and emerging seasonal viral threats.